Gastrointestinal Motility Effects of GLP-1 Receptor Agonists - Bellavance, Danielle; Chua, Samantha; Mashimo, Hiroshi (Current gastroenterology reports, 2025)
Purpose of Review This review summarizes the current understanding of the physiologic influence of GLP-1 RAs on gastrointestinal motility, highlights key clinical implications of these effects, and defines areas for future investigation. Recent Findings Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have revolutionized the treatment of diabetes and obesity and are increasingly being identified as promising therapies for a wide range of conditions. GLP-1 RAs mimic naturally occurring GLP-1, an enterohormone produced in response to oral intake that regulates glucose metabolism and promotes weight loss. While GLP-1 RAs target a wide range of organ systems, their impacts on gastrointestinal motility are widely regarded as a major mechanism by which they exert their metabolic effects. However, the drugs’ alterations in gut motility may account for many of their commonly reported adverse effects including nausea, vomiting, early satiety, dyspepsia, and bowel habit changes. Summary GLP-1 RAs alter gastrointestinal motility at all levels of the GI tract, with delayed gastric emptying being the most well characterized. The effects of GLP-1 RAs on gastrointestinal motility have important clinical implications, including possible increased periprocedural aspiration risk and potential challenges with medication adherence and tolerability.